Cardiovascular Implications of Coronavirus Disease 2019: Review of Current Literatures - Rissa Ummy Setiani; Bayushi Eka Putra; Rini Istisakinah; Ruth Grace Aurora; Amanda Halimi (Jurnal Kardiologi Indonesia, 2020)
The coronavirus disease-2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) that first appeared in Wuhan, China. COVID-19 was found to have significant connection with the cardiovascular system by causing complications such as myocarditis and arrhythmias. Furthermore, medications for COVID-19 have been shown to induce cardiovascular side effects. The emergence of COVID-19 spreading also raised questions on the need for modification of life support algorithms to protect vulnerable healthcare workers.